A Cross-Sectional Study of Epidemiological and Clinical Aspects of Pityriasis Rosea along with Dermoscopic Analysis and Histopathology Correlation - Aditi A. Shende; Siddhi B. Chikhalkar (Wolters Kluwer Medknow Publications, 2024)
Background: Pityriasis Rosea (PR) is a common, yet enigmatic, dermatological condition characterized by a distinctive clinical presentation. Despite its prevalence, the aetiology and pathogenesis of PR remain elusive. Aims: To study the epidemiological and clinical aspects of patients with PR. To study dermoscopic findings and carry out histopathological correlation. Methods: A cross-sectional study of 50 patients was conducted. A detailed clinical history was taken and an examination was done followed by a dermoscopy. Quantitative data like age and duration of disease are presented with the help of standard deviation. Qualitative risk factors, like gender, age groups, symptomatology, site of lesion, findings or cutaneous examination, dermoscopy findings, and histopathology findings, are presented with the help of frequency and percentages. Results: PR shows male preponderance and mean age of occurrence being 30.8 ± 15.7 years. Forty per cent of patients had an atypical clinical presentation. The most frequently seen dermoscopy findings were diffuse red background (58%), peripheral collarette scale (62%), and peripheral dotted vessels (50%). On histopathology, the most common findings were spongiosis (44%), parakeratosis (38%), irregular acanthosis (34%), perivascular lymphocytic infiltrate (56%), and red blood cell extravasation (36%). Limitations: Sample size was less due to COVID. As this was a corss-sectional study follow up of patients could not be done. Conclusion: While the diagnosis of PR is clinical, it is difficult in atypical cases where dermoscopy comes to the aid. It also helps identify the age of lesions, thus helping decide the treatment strategy for patients. Biopsy remains the gold standard in ruling out other differentials of PR.